A Pollen-Expressed Gene for a Novel Protein with an F-box Motif that is Very Tightly Linked to a Gene for S-RNase in Two Species of Cherry, Prunus cerasus and P. avium - Hisayo Yamane; Kazuo Ikeda; Koichiro Ushijima; Hidenori Sassa; Ryutaro Tao (2003)
This study describes a novel F-box protein gene in the S-locus of sour cherry (Prunus cerasus) and sweet cherry (P. avium). The gene showed an S-haplotype-specific sequence polymorphism and the expression was specific to pollen. Genomic DNA blot analysis of eight sweet cherry cultivars with the probe for the F-box protein gene under low stringency conditions yielded RFLP bands specific to the S-haplotypes of each cultivar. We discuss the possibility of the gene for the F-box protein being a candidate for the male determinant of gametophytic self-incompatibility in Prunus.